Comparison between density-based and modulus-based quality control testing for highway compaction practice - Kyaw Pyae; Auckpath Sawangsuriya; Kunawee Kanitpong; Surachet Pravinvongvuth (Pathum Thani : Asian Institute of Technology, 2017)
Paper present and compares the results from as series of situ density-based and modulus- based quality control test that were conducted in field trial section located at the new highway route:Pattaya-Map Ta Phut motorway, the Department of Highways, Thailand. SSG, DCP and LWD are used for modulus based measurement and SDG and sand cone tests are used for density based measurements to determine the compaction quality of the compacted earth fill embankment. Linear regression analysis and coefficient of variation are determined for the comparison. Comparison of the in situ test results illustrate that point-to-point variation is typical for each of these devices to a varying degree for different devices that were ex- amined. No consistent relations between the two alternative quality control tests are found. The measured modulus value correlated poorly to the soil density gauge dry density and moisture content from both SDG and laboratory. Conventional density-based quality con- trol tests cannot describe the variability in modulus of compacted earth fill embankment for compaction quality control. Finally the proposed criteria for using both density-based and modulus-based quality control testing in companion is recommended.
A capstone project report submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Engineering Civil And Infrastructure Engineering, School of Engineering and Technology
Capstone Project (B.Sc.)-Asian Institute of Technology, 2017
Keywords: Density functionals; Compacting Soils